MODERN MANAGEMENT OF PARKINSON’S DISEASE – PHARMACOLOGICAL, SURGICAL, AND NEUROPROTECTIVE APPROACHES - Khakimov M.N. (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: The management of Parkinson’s disease has evolved from solely symptomatic treatment to a multifaceted strategy combining pharmacological therapy, surgical interventions, and multidisciplinary care. This article reviews current treatment options, including emerging neuroprotective and disease-modifying strategies.